The Juridical Study of the Position of Joint Property Due to Divorce According to the Law on Marriage - Khairi, Musthafa (TABELLIUS: Journal of Law, 2023)
This research aims to find out and analyze the evidentiary process and the basic legal considerations used by judges for the distribution of mutually exclusive assets and to understand the legal consequences of dividing mutually exclusive assets for husband and wife resulting from a divorce at the Kendal Religious Court. The research approach used in this thesis is a sociological juridical legal research method. This research uses primary data sources and secondary data sources and then the data is analyzed qualitatively. The type of data used in this research is primary data which includes the 1945 Constitution; Law Number 16 of 2019 concerning amendments, as well as secondary data containing books and other supporting documents. Collecting research data using interview techniques and studying documents or library materials. The data analysis method used in analyzing the data is qualitative analysis. The research results show that the evidentiary process and basic considerations in decisions on joint property cases start from the examination stages, the judge's considerations in his decision are based on evidence. The division of joint assets is carried out in accordance with the provisions of the applicable law. The judge's decision regarding the distribution of joint assets as a result of divorce is in accordance with the applicable rules or regulations. Judging from the applicable legislation, Law Number 16 of 2019 concerning amendments to Law Number 1 of 1974 concerning Marriage and KHI is appropriate, namely that joint assets are divided between the plaintiff and the defendant so that each gets Â½ of the joint assets. Keywords: Marriage, Divorce and Gono-Gini's Assets)